The Influence of Brand Ambassadors, Brand Image and Brand Trust on Purchase Decisions - Firanti Firanti; Lingga Yuliana (Journal of Social Commerce, 2025)
This study investigates the influence of brand ambassadors, brand image, and brand trust on consumer purchasing decisions for Le Minerale bottled water in Indonesia. It aims to understand how these factors collectively shape consumer perceptions and behavior in a competitive FMCG market. This study integrates brand ambassador, brand image, and brand trust into a single model to explain purchasing decisions, highlighting that brand trust and brand image are more influential than brand ambassadors, providing practical insights for FMCG marketing strategies. A descriptive quantitative approach using surveys was applied. Data were collected from 200 respondents in the Greater Jakarta area who had purchased or used Le Minerale products, selected through purposive sampling. A five-point Likert scale questionnaire was used, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Findings reveal that brand ambassadors have a positive but insignificant effect on purchasing decisions, suggesting that celebrity endorsements alone do not strongly influence consumer behavior. Meanwhile, brand image and brand trust significantly and positively affect purchases, with brand trust showing the strongest effect. This emphasizes the importance of consumer confidence in product quality and reliability in motivating purchase decisions. Strengthening brand image and consumer trust can help Le Minerale increase market share, encourage repeat purchases, and enhance the competitiveness of Indonesia’s bottled water industry. These strategies contribute to economic growth by fostering a sustainable and competitive local FMCG sector.